VD_FINDINFO Décision / 2023 / 620 vom 11. Juli 2023 - VD Tribunal cantonal (2023)
DIFFAMATION, CALOMNIE, ORDONNANCE DE CLASSEMENT, MENACEDROIT PÉNAL, PREUVE DE LA VÉRITÉ | 173 CP, 174 CP, 180 CP, 319 al. 1 CPP